Pengaruh Prinsip Syariah terhadap Penerapan Teknologi dalam Akuntansi Modern: The Influence of Sharia Principles on the Application of Technology in Modern Accounting - Arlena Maudina; Defia Eka Alpianti; Dwi Heni Hendryati; Ellena Prima Hapsari; Filsa Vania Pradisti; Nurulita Aulia Indriyani (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
Sharia principles based on justice, transparency, and trustworthiness, islamic accounting seeks to create a financial reporting system that is not only materially beneficial but also brings spiritual and social good. The application of technology in modern accounting can go hand in hand with sharia principles that can increase efficiency and ensure that the accounting process is in accordance with islamic values. Technology has a significant impact on the islamic economic industry, especially in the field of accounting, as time goes by there are more and more innovations and also new breakthroughs regarding accounting-specific technology. This research confirms the importance of harmonization between sharia principles and technological developments to create an accounting system that is ethical, efficient, and in accordance with the needs of the islamic financial industry.